Phosphorylation of the Porcine Reproductive and Respiratory Syndrome Virus Nucleocapsid Protein - Wootton, Sarah K. (American Society for Microbiology, 2002)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a cytoplasmic RNA virus with the unique or unusual feature of having a nucleocapsid (N) protein that is specifically transported to the nucleolus of virus-infected cells. In this communication, we show that the N protein is a phosphoprotein. Phosphoamino acid analysis of authentic and recombinant N proteins demonstrated that serine residues were exclusively phosphorylated. The pattern of phosphorylated N protein cellular distribution in comparison with that of [(35)S]methionine-labeled N protein suggested that phosphorylation does not influence subcellular localization of the protein. Time course studies showed that phosphorylation occurred during, or shortly after, synthesis of the N protein and that the protein remained stably phosphorylated throughout the life cycle of the virus to the extent that phosphorylated N protein was found in the mature virion. Two-dimensional electrophoresis and acid-urea gel electrophoresis showed that one species of the N protein is predominant in virus-infected cells, suggesting that multiple phosphorylated isoforms of N do not exist.